+0  
 
0
41
1
avatar

How do i simplify this? √6 * √75    &    √12 - √3

Answer according to the key is 15 * √2   &   √3

 

and I'm not allowed to use a calculator obvs

Guest Nov 20, 2018

Best Answer 

 #1
avatar+14578 
+2

sqrt6  *  sqrt 75 =

sqrt6  * sqrt(25*3)=

5 *  sqrt6 * sqrt 3 =

5* sqrt(6*3)

5 sqrt(18)

5 sqrt(9*2)

5(3)sqrt2 = 15 sqrt 2  

 

sqrt12 - sqr3 = sqrt(4*3)-sqrt3 = 2 sqrt3 -sqrt3 = (1)sqrt3 = sqrt3

ElectricPavlov  Nov 20, 2018
 #1
avatar+14578 
+2
Best Answer

sqrt6  *  sqrt 75 =

sqrt6  * sqrt(25*3)=

5 *  sqrt6 * sqrt 3 =

5* sqrt(6*3)

5 sqrt(18)

5 sqrt(9*2)

5(3)sqrt2 = 15 sqrt 2  

 

sqrt12 - sqr3 = sqrt(4*3)-sqrt3 = 2 sqrt3 -sqrt3 = (1)sqrt3 = sqrt3

ElectricPavlov  Nov 20, 2018

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.